New genera and species of Ostracoda from the Maastrichtian and Danian of the Neuquén Basin, Argentina - Ceoilin, Daiane (2015)
A total of 113 species belonging to 54 genera are recovered from a study of the Maastrichtian and Danian deposits in the Cerro Azul section of the Neuqu en Basin, west-central Argentina. Of these, 9 new genera, 38 new species and 28 species in open nomenclature are recorded. These form the basis of the present study and are listed below. Genera: Phelocyprideis gen. nov., Aleisocythereis gen. nov., Apatoleberis gen. nov., Mimicocythereis gen. nov., Castillocythereis gen. nov., Hysterocythereis gen. nov., Orthrocosta gen. nov., Petalocythereis gen. nov. and Sthenarocythereis gen. nov. Species: Cytherella saraballentae sp. nov., Cytherella semicatillus sp. nov., Paracypris bertelsae sp. nov., Paracypris imaguncula sp. nov., Argilloecia abnormalis sp. nov., Argilloecia concludus sp. nov., Argilloecia hydrodynamicus sp. nov., Bythoceratina cheleutos sp. nov., Phelocyprideis acardomesido sp. nov., Eucythere dinetos sp. nov., Krithe crepidus sp. nov., Cytheropteron hyperdictyon sp. nov., Cytheropteron bidentinos sp. nov., Cytheropteron translimitares sp. nov., Aversovalva glochinos sp. nov., Eucytherura stibaros sp. nov., Hemingwayella verrucosus sp. nov., Heinia prostratopleuricos sp. nov., Loxoconcha (s.l.) posterocosta sp. nov., Keijia circulodictyon sp. nov., Keijia kratistos sp. nov., Paramunseyella epaphroditus sp. nov., Munseyella costaevermiculatus sp. nov., Ameghinocythere archaios sp. nov., Aleisocythereis polikothonus sp. nov., Castillocythereis multicastrum sp. nov., Castillocythereis albertoriccardii sp. nov., Cythereis stratios sp. nov., Cythereis clibanarius sp. nov., Cythereis trajectiones sp. nov., Henryhowella (Wichmannella) praealtus sp. nov., Hysterocythereis paredros sp. nov., Hysterocythereis coinotes sp. nov., Hysterocythereis diversotuberculatus sp. nov., Orthrocosta decores sp. nov., Orthrocosta atopos sp. nov., Orthrocosta phantasia sp. nov. and Sthenarocythereis erymnos sp. nov. The nature of the fauna and aspects of its evolution are discussed.